The Word Leading to Agreement - Kowalczyk, Małgorzata; Poslední, Petr (Rocznik Pedagogiczny, 2020)
The concept of the language as an instrument for children, that leads to their mutual understand- ing in the classes 1–3, depends on the comprehensive educators approach to the relations between linguistics and the philosophy of language, developmental psychology, sociology of culture, and the history of the Polish society. The child’s undertaking of the school education imposes on the teacher the obligation to accompany it not only in mastering the elementary knowledge of the native language’s grammar system, but also in creating situations that overcome students fear of making difficult decisions when solving interesting tasks. When using the functions of the language: fatic, communicative, informational, expressive or meta-linguistic, pupils go through the several stages from the incorrect speech to correct speech, and they master the elementary structure of the reading texts intended for the little recipients. The described process would be strengthened depending on the pupil’s social background, and conditioned culturally and environmentally. This in turn affects the perception of the poetic language function and aesthetic attitude towards art.